(3JMaI GdWGdHjf aj eYQaI CMcGe Gdfhf GdSGcfI hGdJfhjfs - (3MSf Hf eMeO GdTGaYj GdNhLG GdNVjQjs ((3eMeO Hf YHOGdSdGe Hf eMeO GdaPjGQj s)
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ Edi QHg GdbOjQ MSf Hf eMeO GdTGaYj GdTgjQ HGdNhGLG Ke GdNVjQj gP fHPI dWjaI JJYdb HCMcGe Gdfhf GdSGcfI hGdJfhjf s
(3BNQgG (B:s
(3hGdbSe GdKGfj hLH Ydjg Gf jajO eG bHdg hGddg SHMGfg hJYGdi CYde s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3QhGb GdeZGQHI (B- (3GdCRgQ (B(442) s
Keywords: (3GdbQGAGJ hGdJLhjOs